Catheter-Directed Thrombolysis With a Continuous Infusion of Low-Dose Alteplase for Subacute Proximal Venous Thrombosis: Efficacy and Safety Compared to Urokinase. (November 2018) - Gong, Maofeng; He, Xu; Song, Jinhua; Zhao, Boxiang; Shi, Wanyin; Chen, Guoping; Gu, Jianping
The purpose of this study was to compare the efficacy and safety associated with catheter-directed thrombolysis (CDT) using either recombinant tissue plasminogen activator (rt-PA) or urokinase (UK) for subacute deep venous thrombosis (DVT). From January 2014 to December 2016, we conducted a retrospective analysis on a total of 49 patients who underwent consistent CDT with either rt-PA (rt-PA-CDT group) or UK (UK-CDT group) treatment. The thrombolytic rate of the rt-PA-CDT group was significantly higher than that of the UK-CDT group (87.5% vs 60%, respectively; χ 2 = 4.751; P = .029). The rt-PA-CDT group exhibited an improved grade III thrombolytic rate (9 patients vs 3 patients; χ 2 = 5.144; P = .023). The time for the rt-PA-CDT group to achieve a grade III thrombolytic rate was shorter than that of the UK-CDT group (5.01 ± 1.09 days vs 6.43 ± 1.69 days, respectively; t = −2.187; P = .044). No severe complications were seen in either group and mild complications rates were 16.7% and 20.0% (χ 2 = .091; P = .763). The clinical efficacy rates at discharge were 91.7% and 76.0%, respectively (χ 2 = 2.200; P = .138). In conclusion, CDT with a continuous infusion of low-dose rt-PA resulted in safe and effective thrombolysis in the great majority of patients with proximal DVT in the subacute phase. Furthermore, rt-PA was significantly better than UK in terms of the thrombolytic rate. In our study, rt-PA-CDT improved the thrombolytic rate of grade III thrombus and achieved a grade III thrombolytic rate in a shorter time than UK-CDT.